Platinum-Catalyzed Regioselective Dehydrogenative Homocoupling of Dimethyl Phthalate for the Direct Synthesis of Sym-BPTT - Ishikawa, Soya; Iseki, Katsuhiko; Ishitani, Haruro; Kobayashi, Shū (Sustainability & Circularity NOW, 2025)
A novel synthesis method for sym-BPTT, an important synthetic intermediate for electronic materials, is reported. This method features a platinum-catalyzed regioselective dehydrogenative homocoupling of dimethyl phthalate. Unlike previous palladium-catalyzed methods, this reaction proceeds with high regioselectivity without requiring any ligands when an appropriate reoxidation system is employed, thus simplifying the purification process. While the yield is currently lower than that of existing methods, this study demonstrates the potential of platinum catalysts for dehydrogenative homocoupling reactions. A preliminary continuous-flow system for this homocoupling reaction was also developed, although the yield was low, and regioselectivity was not well-controlled.
Keywords: Platinum catalyst; Dehydrogenative homocoupling; Continuous-flow synthesis